Regionalisation of major trauma services in England: a post-implementation analysis. (25th February 2016) - Metcalfe, David; Perry, Daniel; Bouamra, Omar; Woodford, Maralyn; Edwards, Antoinette; Salim, Ali; Lecky, Fiona; Costa, Matthew
Abstract: Background: There is strong evidence that severely injured patients are optimally treated within inclusive trauma networks. One feature of such networks is prehospital triage of the most injured patients to designated trauma hospitals. In April, 2012, major trauma services across England were reconfigured into regional trauma networks based around designated major trauma centres (MTCs). This study explored the early effects of the regionalisation of major trauma services in England. Methods: The Trauma & Audit Research Network (TARN) identified severely injured patients treated in the 9 months before and after each MTC became fully operational. Outcomes included quality indicators (eg, time to CT scanning for head injured patients) and clinical outcomes (eg, in-hospital mortality). Completeness of the TARN dataset was quantified with Hospital Episode Statistics. Death registrations were used to identify any change in the overall number of traumatic deaths in England. Findings: The number of severely injured patients treated in MTCs increased from 7705 to 12 476. All care quality indicators improved: treatment by a consultant (30·4% before MTC vs 54·3 after MTC, p<0·0001), administration of tranexamic acid to bleeding patients (17·0% vs 58·5, p=0·006), and time to CT scanning for head injured patients (49·2 min vs 31·2, p<0·0001). Fewer patients required secondary transfer between hospitals (31·3% vs 25·9, p<0·0001) and a greater proportion were discharged with a Glasgow Outcome Scale of good recovery (52·4% vs 64·5, p<0·0001). There were no differences in either crude or adjusted mortality between the periods for all patients or for those with an Injury Severity Score of more than 15. The overall number of traumatic deaths in England did not change. Interpretation: There is early evidence of improved care associated with trauma service regionalisation, including some process measures, enhanced case reporting for national audit, and reduced need for secondary transfer of patients between hospitals. However, in this early post-implementation analysis, significant reductions in patient mortality were not observed. Funding: Royal College of Surgeons of England Fulbright Scholarship.